Factors Associated with HIV Preventive Behavior in Loading-Unloading Workers at Tenau Port Kupang - Filmon Salan; Imelda Manurung; Helga J. N Ndun (Universitas Nusa Cendana, 2020)
Human Immuno Deficiency Virus (HIV) is a virus that attacks the immune system and further weakens the body to fight disease. The port is a strategic area with the potential for the spread of HIV cases. The aim of this study is to determine the factors associated with behavior to prevent HIV incidence in TKBM in the port of Tenau Kupang. This study used an analytical survey method with a cross-sectional study approach. The sample in this study consisted of 68 TKBM workers. The data analysis used was a bivariate analysis with a chi-square statistical test. The results of this study showed that behavior to prevent HIV incidence was related to knowledge (ρ = 0.016) and social environment (ρ = 0.008), while attitudes (ρ = 0.718) and distance from service (ρ = 0.181 ) are not related to behavior to prevent HIV incidence. HIV education and health promotion are appropriate preventive measures to reduce the incidence of HIV transmission.